The Impact of Social Media Marketing and Endorsement on Purchasing Decisions at Daarul Jannah Cottage - Caca Komara; Muji Rahayu (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The central aim of this study is to analyze social media marketing (SMM) and the use of endorsements influence purchasing decisions at Cottage Daarul Jannah, a sharia-based accommodation. Using a purposive sampling technique, 50 customers were selected as respondents, and data were obtained through questionnaires measuring aspects of SMM, endorsement, and purchase decision. The findings revealed that both variables influence purchasing decisions, positively and significantly, both individually and simultaneously. The findings suggest that the implementation of digital marketing strategies through social media, as well as the use of endorsements from influencers, can increase customer interest and strengthen their decision to make a purchase. Therefore, the optimization of digital marketing strategies has the potential to be a crucial element in improving competitiveness and building customer loyalty in the hospitality industry.